Career Satisfaction: A Look behind the Races - Yap, Margaret; Cukier, Wendy; Holmes, Mark; Hannan, Charity-Ann (Relations industrielles / Industrial Relations, 2010)
Previous studies have largely focused on the career success of white employees (Heslin, 2005). Using recent survey data, this paper examines the career satisfaction levels of white/Caucasian and visible minority managerial, professional and executive employees in the information and communications technology [ICT] and financial services sectors in corporate Canada. Given that the demographic makeup of organizations in Canada is drastically changing with the aging population and the increasing participation of visible minorities in the labour force, it is crucial for managers and organizations to understand their employees’ level of career satisfaction. Studies have found that employees who are more satisfied with their careers are more engaged and thus are more likely to actively contribute to the organization’s success (Peluchette, 1993; Harter, Schmidt and Hayes, 2002). Findings from this paper showed that the average career satisfaction scores were lower for visible minority employees than for white/Caucasian employees. In addition, variations were found between white/Caucasian employees and Chinese, South Asian and Black visible minority employees. While Black employees were 13.0% less satisfied than white/Caucasian employees, Chinese employees were only 8.3% less satisfied than their white/Caucasian counterparts, and the difference between South Asian and white/Caucasian employees was found to be insignificant. Decomposition analyses show that over 58% to 82% of the difference in career of satisfaction scores, depending on the ethnic group, can be accounted for by factors included in this paper. Of the unexplained portion, most of the differences in career satisfaction between white/Caucasian and minority groups are attributable to higher returns to white/Caucasian employees’ human capital and demographic characteristics.